2017
DOI: 10.1111/jav.01267
|View full text |Cite
|
Sign up to set email alerts
|

Elevational replacement of two Himalayan titmice: interspecific competition or habitat preference?

Abstract: Elevational species replacement is a widely documented pattern in montane species. Although interspecific competition has been shown to be important in setting species elevational limits in tropical habitats, its effect in species of temperate regions is poorly studied. We tested the role of interspecific competition for space in the breeding season and for food in the non‐breeding season in mediating the distribution of two resident titmice species in the Himalayas. We show that high elevation green‐backed ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Our findings contrast with earlier suggestions that congeneric competition is an important driver of elevational zonation among tropical birds (Freeman et al, 2019; Terborgh & Weske, 1975) and instead align with studies that found only scarce evidence for congeneric competition among montane bird communities (Barve & Dhondt, 2017; Dehn & Christiansen, 2001; Elsen et al, 2017; Jankoswki et al, 2010). We found that all congeneric species overlapped to some extent in their elevational ranges (see ranges in Table S1) and it is likely that other forms of niche partitioning (e.g., regarding diets or the location of reproductive sites) account for these levels of sympatry (Elsen et al, 2017).…”
Section: Discussioncontrasting
confidence: 98%
“…Our findings contrast with earlier suggestions that congeneric competition is an important driver of elevational zonation among tropical birds (Freeman et al, 2019; Terborgh & Weske, 1975) and instead align with studies that found only scarce evidence for congeneric competition among montane bird communities (Barve & Dhondt, 2017; Dehn & Christiansen, 2001; Elsen et al, 2017; Jankoswki et al, 2010). We found that all congeneric species overlapped to some extent in their elevational ranges (see ranges in Table S1) and it is likely that other forms of niche partitioning (e.g., regarding diets or the location of reproductive sites) account for these levels of sympatry (Elsen et al, 2017).…”
Section: Discussioncontrasting
confidence: 98%
“…Thermoregulatory ability is just one of many factors, biotic and abiotic, and the interactions between the two, that ultimately drive the elevational distribution of a montane bird (McCain 2009, Cadena et al 2012, Jankowski et al 2013, Barve and Dhondt 2017. Avian thermoregulation in itself is complex, ranging from behavioral (Barçante et al 2017) to molecular adaptations (Stager and Cheviron 2020) for surviving cold stress.…”
mentioning
confidence: 99%
“…In the model that included latitudinal zone, the estimate for tropical species-pairs was positive and did not overlap zero, indicating that the tendency for lower elevation species to be more aggressive in playback studies was associated with the tropics (Figure 3; the estimate for the subgroup of temperate zone species-pairs was approximately zero). While most studies conducted either direct observations or playback experiments, there were two studies that measured interspecific aggression using both direct observations and playback experiments, and these two studies both reported congruent results between the two methodologies (Pasch et al , 2013; Barve & Dhondt, 2017).…”
Section: Resultsmentioning
confidence: 99%